THE RELATIONSHIP BETWEEN THE TECHNOSTRESS CREATORS FACTORS AND THE PERCEIVED QUALITY OF INFORMATION TECHNOLOGY SERVICES - Marchiori, Danilo Magno; Mainardes, Emerson Wagner (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This research presents the relationship between the technostress creators factors and the perceived quality of the services provided by internal information technology departments. To this end, multiple linear regressions were performed, from a sample containing 927 responses of IT service users. The participants work in 14 different Brazilian public institutions, allocated throughout the 5 regions of the country and are strongly dependent on information technology in their business processes. The results show that the service delivery, the service product and the service environment have explanatory power on the overall quality of services. In addition, data revealed that techno-invasion, the technostress creator factor referring to users’ feeling that their personal life is being invaded by information technology, was negatively related to the general quality of service.